Peptide-Based Targeting of the L-Type Calcium Channel Corrects the Loss-of-Function Phenotype of Two Novel Mutations of the CACNA1 Gene Associated With Brugada Syndrome - Di Mauro, Vittoria; Ceriotti, Paola; Lodola, Francesco; Salvarani, Nicolò; Modica, Jessica; Bang, Marie-Louise; Mazzanti, Andrea; Napolitano, Carlo; Priori, Silvia G.; Catalucci, Daniele (Frontiers in Physiology, 2021)
Brugada syndrome (BrS) is an inherited arrhythmogenic disease that may lead to sudden cardiac death in young adults with structurally normal hearts. No pharmacological therapy is available for BrS patients. This situation highlights the urgent need to overcome current difficulties by developing novel groundbreaking curative strategies. BrS has been associated with mutations in 18 different genes of which loss-of-function (LoF) CACNA1C mutations constitute the second most common cause. Here we tested the hypothesis that BrS associated with mutations in the CACNA1C gene encoding the L-type calcium channel (LTCC) pore-forming unit (Cavα1.2) is functionally reverted by administration of a mimetic peptide (MP), which through binding to the LTCC chaperone beta subunit (Cavβ2) restores the physiological life cycle of aberrant LTCCs. Two novel Cavα1.2 mutations associated with BrS were identified in young individuals. Transient transfection in heterologous and cardiac cells showed LoF phenotypes with reduced Ca2+ current (ICa). In HEK293 cells overexpressing the two novel Cavα1.2 mutations, Western blot analysis and cell surface biotinylation assays revealed reduced Cavα1.2 protein levels at the plasma membrane for both mutants. Nano-BRET, Nano-Luciferase assays, and confocal microscopy analyses showed (i) reduced affinity of Cavα1.2 for its Cavβ2 chaperone, (ii) shortened Cavα1.2 half-life in the membrane, and (iii) impaired subcellular localization. Treatment of Cavα1.2 mutant-transfected cells with a cell permeant MP restored channel trafficking and physiologic channel half-life, thereby resulting in ICa similar to wild type. These results represent the first step towards the development of a gene-specific treatment for BrS due to defective trafficking of mutant LTCC.